ANALISA PEMANFAATAN PASIR SUNGAI DIKABUPATEN PESISIR SELATAN - Arman. A; Julva Adri Angel (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
This research was conducted to find out how the quality of river sand from the Batang Salido and Nanggalo Tarusan. In addition, research is also conducted to find out how the influence of river sand from the two regions on the compressive strength of the concrete produced. Test specimens were made 9 pieces for each type of fine aggregate for testing the age of 7 days, 14 days and 28 days with compressive strength K225 plan. From the test results it is evident that the use of both sand has low organic content. In addition, in the process of making test specimens there is sludge which is in the test specimens mixture. Therefore, there are many cavities when the mold of the test object is opened, which results in a low compressive strength of the test object.